Prevalence and Associated Family Factors of Sibling Bullying Among Chinese Children and Adolescents - Qing, Zaihua; Ma, Yankun; Liu, Xiaoqun (Frontiers in Psychology, 2022)
Sibling bullying is the most common form of aggression within family worldwide, while the prevalence and correlations of sibling bullying is little known in China. The current research focused on the association between family factors and sibling bullying among Chinese adolescents, and explore sex differences in sibling bullying in the context of Chinese culture. A cross-sectional study was conducted to explore the characteristics of sibling bullying by sampling 6302 children and adolescents who had at least 1 sibling living in the household. Of the participants, 1827 (29.0%) were involved in sibling bullying over the past half year, and pure victims, pure bullies, and bully-victims were 486 (7.7%), 510 (8.1%), and 831 (13.2%), respectively. Family factors of sibling bullying were partly different between boys and girls. Parental absence of both father and mother was a risk factor of being a pure bully and a bully-victim for boys, and of being a pure victim for girls. Parental son preference increased the odds of being a pure victim and a bully-victim for boys, and of being all roles of sibling bullying involvement for girls. Besides, parent–parent violence, parent–child violence, and living with a single parent were risk factors of sibling bullying. The results underline the importance of home environment on sibling relationship, and intervention of sibling bullying should include improving family climate.